2012
DOI: 10.1021/nn300757t
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Intercalation Replacement and Selective Functionalization of Graphene Nanoribbon Stacks

Abstract: A cost-effective and potentially industrially scalable, in situ functionalization procedure for preparation of soluble graphene nanoribbon (GNRs) from commercially available carbon nanotubes is presented. The physical characteristics of the functionalized product were determined using SEM, evolved gas analysis, X-ray diffraction, solid-state (13)C NMR, Raman spectroscopy, and GC-MS analytical techniques. A relatively high preservation of electrical properties in the bulk material was observed. Moreover, replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
181
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 114 publications
(187 citation statements)
references
References 38 publications
6
181
0
Order By: Relevance
“…2a). To date, there have been several studies on graphene functionalization 14,16,23,24 based on the chemistry of donor-type graphite intercalation compounds. Nevertheless, most approaches demonstrate only a very low amount of functionalization (thus poor dispersibility), which is in good agreement with the early works of Bergbreiter and Killough.…”
Section: Preparation Of Ink With Functionalized Graphenementioning
confidence: 99%
“…2a). To date, there have been several studies on graphene functionalization 14,16,23,24 based on the chemistry of donor-type graphite intercalation compounds. Nevertheless, most approaches demonstrate only a very low amount of functionalization (thus poor dispersibility), which is in good agreement with the early works of Bergbreiter and Killough.…”
Section: Preparation Of Ink With Functionalized Graphenementioning
confidence: 99%
“…While both types of bottom-up approaches can achieve better control of the structures of GNRs, the complexity in the synthesis procedures and the relatively low yields are not ideal for mass production in large-scale applications. [3] Unzipping carbon nanotubes (CNTs): Multi-walled CNTs can be unzipped along the longitudinal direction to form GNRs [36,37]. Compared to the first two methods, this approach has the potential of mass production and lower costs.…”
Section: Introductionmentioning
confidence: 99%
“…The GNRs are 10-20 nm in width and consist of single-, bi-and tri-layer graphene. A potassium intercalation method is also used to longitudinally split the CNTs by James M. Tour [73]. Parashar et al reported a catalytic unzipping of CNTs method, based on the solubility of carbon atoms in nickel, to synthesize GNRs [70].…”
Section: Top-down Methodsmentioning
confidence: 99%